Impact of the climatic change on animal diseases spread: the example of bluetongue in Spain - Sánchez-vizcaíno Rodríguez, J.M.; Cianci, C.; Granero Belinchon, R.; Picado Alvarez, R.; Pino Carrasco, F.J.; Rodrigo Campos, N.; Tamayo Mas, E.; Vázquez, M.; Ivorra, B.; Martínez-López, B.; Ramos, A.M. (Revista Complutense de Ciencias Veterinarias, 2011)
Climate change is affecting the ecosystem and many of the factors associated with human and animal diseases. In particular, significant changes in insect-borne diseases have been shown. The clearest example is found in Europe regarding the bluetongue virus (BTV), a disease of ruminants transmitted by insects (Culicoides spp.). Traditionally this disease was distributed below the 40th parallel, but since 2006 spread to northern Europe where the situation is now endemic. This spread of BTV has been produced by several factors. First, there is a direct relationship between the increased of temperature and the presence of Culicoides. It is also important to highlight the role of the wind in the movement of insects, and could be a significant mode of transmission of vector-borne diseases (such as bluetongue) from endemic areas to free areas. In Spain, the introduction of Culicoides by the wind has not formally been proved, but many experts and epidemiological data has hypothesized it, especially in the first outbreaks occurred in 2004 in the Iberian Peninsula. The objective of the model described here has been, first, to predict the number of Culicoides introduced by the wind and its potential survival in Spain and, secondly, to assess the impact that a potential increase in temperature could have on the distribution and survival Culicoides in Spain. This model will help to identify locations and time periods at highest risk for mosquitoes introduction and survival, and will help to optimize efforts and better prevent and control future outbreaks of bluetongue in the country.
Keywords: Modeling; Wind spread; Bluetongue; Climate change